VARIABILITY OF THE SEMANTIC STRUCTURE OF ORAL SPONTANEOUS TEXT DEPENDING ON THE SPEAKER’S AGE (Philological Studies, 2019)
The paper deals with an original understanding of the semantic structure of text; a model of the semantic structure of text is constructed by method of graphical semantic modeling using a modified method for classifying components. The variability of constructed model is studied depending on the age of informants.
Keywords: text, semantic structure of text, oral text, spontaneous text, social variability, age